Buybacks in treasury cash and debt management - Kenneth D. Garbade; Matthew Rutherford (Federal Reserve Bank of New York, 2007)
This paper examines the use of buybacks in Treasury cash and debt management. We review the mechanics and results of the buyback operations conducted in 2000-01, during a time of budget surpluses, and assess the prospective use of buybacks in the absence of a surplus. Possible future applications include (i) managing the liquidity of the new-issue markets when deficits are declining (by allowing Treasury officials to postpone a decision to discontinue a series without also being compelled to shrink new-issue sizes); (ii) actively promoting the liquidity of the new-issue markets (by repurchasing outstanding debt on a regular basis and funding the purchases with larger offerings of new debt); (iii) limiting the accumulation of large Treasury cash balances (for example, in the second half of April and early May, when many taxpayers make final payments of taxes on income earned in the prior year); and (iv) smoothing week-to-week fluctuations in Treasury bill offerings.
Keywords: G2; H6; 330; buybacks; reverse auctions; debt management; Aktienrückkauf; Auktion; Debt Management; USA